The Effect of Integrated STEM Quantum Learning on Mathematical Reasoning and Conceptual Understanding as Viewed from Gender - Nurus Suhliyatin; I Nyoman Jampel; I Gede Ratnaya (Didaktika: Jurnal Kependidikan, 2025)
This study investigates the effect of the Quantum Learning model integrated with STEM Education on students' mathematical reasoning and conceptual understanding, with a focus on gender differences. The research employed a quasi-experimental design with Randomized Block Design involving 50 students of MTs SA Nurul Qona'ah in the academic year 2023/2024, divided into experimental and control groups. The experimental group received instruction through Quantum Learning integrated with STEM, while the control group followed conventional teaching methods. Data were collected using validated essay-type tests measuring higher-order thinking skills. The results showed that students taught with the integrated model achieved significantly higher scores in both mathematical reasoning and conceptual understanding compared to those taught conventionally. Furthermore, male students outperformed female students in mathematical reasoning, while no significant gender difference was found in conceptual understanding. The model also proved effective for both male and female students individually, with male students generally showing greater gains in reasoning and female students demonstrating better conceptual understanding in conventional settings. These findings suggest that integrating Quantum Learning with STEM creates a meaningful and equitable learning environment that supports higher-order thinking and addresses gender-specific learning needs. The implications of this research highlight the importance of adaptive, student-centered instruction supported by schools, and the need for continued teacher innovation in implementing interdisciplinary, project-based mathematics education.